Wilkie's syndrome caused by exogenous hyperthyroidism in a patient with primary autoimmune hypothyroidism: a case report and literature review - Cervantes Pérez, Enrique (2020)
Wilkie's syndrome or superior mesenteric artery syndrome is an unusual cause of proximal intestinal obstruction, primarily attributed to recent weight loss. We report the case of a 19-year-old woman comes to our clinic and reports weight loss, abdominal pain, nausea, and vomiting. Laboratory tests revealed anemia, hypoalbuminemia, hypomagnesemia, and asuppressed thyroid stimulating hormone secondary to levothyroxine. A barium swallow test showed gastric dilatation, delayed gastric emptying and an axial computed tomography revealed an aortomesenteric angle of 11.7°. Conservative management with total parenteral and enteral nutrition was initiated, being the first-line treatment. In refractory cases surgery is a safe and effective option.